Experimental determination of flame length of buoyancy-controlled turbulent jet diffusion flames from inclined nozzles. (25th January 2016) - Tao, Changfa; Shen, Yan; Zong, Ruowen
Highlights: Flame length addressing the effect of inclined angle for the jet flames. The entrainment constant parameter C1 is generally proportional to cos θ 0 linearly. A global model is proposed for flame length of jet flames from inclined nozzles. Abstract: Flame length of buoyancy-controlled turbulent jet diffusion flames from inclined nozzles with inclined angles of 0°, 30°, 45°, 60°, and 90° to the horizontal has been investigated experimentally in this work. The jet diffusion flames are produced by the nozzles with diameters of 8, 12, and 16 mm. The relationship between flame length and heat release rate has been proposed for jet flames from inclined nozzles. It is found that the values of the entrainment coefficient C 1 are generally proportional to cos θ 0 linearly. A global model when Froude number is below about 300 ( Fr < 300) is developed for estimating the flame length of the buoyancy-controlled jet flames from inclined nozzles.